1998
DOI: 10.1385/endo:8:2:193
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Induces Tyrosine Phosphorylation of Shc and Stimulates Shc/GRB2 Association in Insulin-Sensitive Tissues of the Intact Rat

Abstract: Shc is a novel type of tyrosine-phosphorylated protein activated in response to a wide variety of polypeptide ligands. In this study, we used immunoprecipitation and immunoblotting to examine the effect of insulin on Shc tyrosine phosphorylation and Shc/GRB2 association in insulin-sensitive tissues of the intact rat. Following an infusion of insulin, Shc was tyrosine-phosphorylated in the liver, skeletal muscle, and adipose tissue in a time- and dose-dependent fashion, which peaked 5 min after exposure to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
3
11
0
1
Order By: Relevance
“…Shc and ERK-1/2 phosphorylation Consistent with previous reports [26,27], we found no detectable phosphorylation in the p46 and p66 isoforms of Shc. As shown in Fig.…”
Section: Akt Activationsupporting
confidence: 93%
“…Shc and ERK-1/2 phosphorylation Consistent with previous reports [26,27], we found no detectable phosphorylation in the p46 and p66 isoforms of Shc. As shown in Fig.…”
Section: Akt Activationsupporting
confidence: 93%
“…Furthermore, there is a kinase activity of the insulin receptor towards immunopurified Shc. We have previously demonstrated that insulin induces Shc tyrosine phosphorylation in rat tissues, and a kinase activity of the insulin receptor towards Shc was also suggested (15). The results presented here clearly demonstrate that the insulin receptor is able to induce tyrosine phosphorylation of immunopurified Shc.…”
supporting
confidence: 74%
“…By immunoblotting with specific antibodies it was previously demonstrated that these bands correspond to IRS-1 and IRS-2 which probably were bound to the insulin receptor after insulin stimulation (15).…”
mentioning
confidence: 98%
“…IRS proteins undergo marked tyrosine phosphorylation in response to stimulation of insulin receptors and thereby provide docking sites for PI 3-kinase and the protein-tyrosine phosphatase SHP-2, the latter of which upregulates Ras activity (43). Furthermore, insulin receptors phosphorylate the adapter molecule SHC (44), which is a potent activator of the Ras-mitogen-activated protein kinase pathway. These insulin receptor-evoked positive signals to Ras may therefore have masked Dok-1 regulation of Ras activity in the study of Noguchi et al (42).…”
Section: Resultsmentioning
confidence: 99%